Dynamics of relationships between mentors and beginning teachers - Stoichici (Iavorschi), Elena; Ioniță (Cristea), Anca Elena (Technium Social Sciences Journal, 2022)
This research investigates the relationships that are established between mentor teachers (PM) and beginning teachers (PD) in order to insert the beginning teachers into the school organization and how they are influenced by the institutional management. The specific objectives of the research were the following: (1) Identifying the perception of beginning teachers regarding the difficulties of adapting to the demands of the school environment; (2) Identifying the perception of mentor teachers who work with beginning teachers on the activities of a quality mentorship; (3) Making correlations between the opinions of mentors and novice teachers regarding their strengths and the ability to face adaptation difficulties; The qualitative design consisted of conducting two focus groups with PD and PM. The debut period is considered the most decisive stage in a teacher's professional life. From the first day of school, PD faces the teaching reality that often differs from the perceptions of the teaching profession developed during initial training. The research shows that the teachers in the sample experienced: establishing teacher authority and self-positioning as a teacher, time management, problems with discipline in a classroom, lack of skills to develop curriculum and lesson plans, difficulties in communicating with parents. The article includes critical analysis, opinions on the contradiction at the moment between the legislation and the reality at the school level on the didactic mentoring and the PD insertion.